The Impact of Artificial Intelligence (AI) -Based Marketing and Lifestyle Changes on Purchasing Decisions for Samsung Galaxy Flip5 Smartphones - Dayang Dea Dwi Sari; Tezar Arianto; Mimi Kurnia Nengsih; Ade Tiara Yulinda (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study aims to examine the impact of Artificial Intelligence (AI) -based marketing and lifestyle changes on purchasing decisions for Samsung Galaxy Flip 5 smartphones. The research adopts a quantitative approach, involving a sample of 110 respondents who utilize AI features on Samsung devices at Toko Jaya Ponsel Bengkulu. The results indicate that AI-based marketing and lifestyle changes have a positive and significant influence on purchasing decisions, both partially and simultaneously. Specifically, the findings reveal that AI-based marketing and lifestyle changes account for 24.1% of the variance in purchasing decisions. These findings have strategic implications for Samsung and Toko Jaya Ponsel Bengkulu, emphasizing the importance of leveraging AI-based marketing strategies and understanding consumers’ evolving lifestyles to enhance sales performance.